1984
DOI: 10.1007/bf00217870
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of ferritin-concanavalin A by the lactating mammary cell in vivo

Abstract: Ferritin-concanavalin A (Fer-Con A) was used to label the apical plasma membrane of the lactating cell to determine whether membrane internalization takes place. Rat glands were infused in vivo via the teat with 0.2 mg of Fer-Con A in 0.2 ml tris buffer (pH 7.0) containing 0.1% trypan blue, the latter acting as a marker of the infusate. Tissues were obtained from separate animals 5, 10 and 60 min postinfusion. Fer-Con A was seen in alveolar lumina bound to the outer surfaces of apical plasma membrane, microvil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Ferritin was detected in secretory vesicles that may have derived from small ferritin-labelled vesicles observed in close proximity to, and apparently fusing with mature secretory vesicles (see, for example, Fig. 3b of Welsch et al 1984). This observation raises the intriguing possibility that the MUC1-containing vesicles seen in close association with secretory vesicles in this study (Fig.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Ferritin was detected in secretory vesicles that may have derived from small ferritin-labelled vesicles observed in close proximity to, and apparently fusing with mature secretory vesicles (see, for example, Fig. 3b of Welsch et al 1984). This observation raises the intriguing possibility that the MUC1-containing vesicles seen in close association with secretory vesicles in this study (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…However, much of this vesicle-associated MUC1 may have recycled from the cell surface. Evidence for this latter possibility is provided by the earlier studies of Welsch et al (1984) who showed that concanavalin A/ferritin conjugates, infused via the nipple into the mammary glands of lactating rats, bound to the apical plasma membrane and were then internalised in vesicles. Ferritin was detected in secretory vesicles that may have derived from small ferritin-labelled vesicles observed in close proximity to, and apparently fusing with mature secretory vesicles (see, for example, Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…An endosomal recycling pathway has been demonstrated by the accumulation of endocytosed fluorescent transferrin in a vesicular compartment near the basal membrane of the alveolar cells in MEC from lactating mice incubated in vivo with a bath solution (Zhang et al, 2000). Moreover, a subapical endosomal compartment, closely related to the endocytic-secretory pathway, has been demonstrated in lactating rat MEC (Welsch et al, 1984). Lastly, the transfer of a lipoproteincontaining particle, from the serum, across the mammary epithelium into the milk of lactating mice, has been demonstrated (Monks et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…1) [13, 52, 53]. The mechanisms of transcytosis involve a series of complex sorting events in the basolateral early endosome and the common endosome recycling (CER) compartments that intersect with Golgi and secretory vesicle pathways (pathway10) [5456]. Consequently, transcytosis provides mechanisms for transferring basolateral membrane phospholipids, which are distinct from apical membrane phospholipids and enriched in PC [5], to multiple internal membrane compartments as well as to the apical plasma membrane.…”
Section: Introductionmentioning
confidence: 99%